Tubular Microdiscectomy versus Conventional Surgery for Sciatica. A Comparative Prospective Enzyme Study - Cherkaoui, Mandour; Jalal, Kasouati; Jawad, Laaguili; Miloudi, Gazzaz; Brahim, El Mostarchid (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objective Muscle injury is inevitable during surgical exposure of the spine, and it is quantified by the release of creatine phosphokinase. The aim of the present study is to make a comparison between tubular microdiscectomy and conventional microdiscectomy by using the pre- and postoperative serum concentrations of creatine phosphokinase as an indicator of muscle injury.Materials and Methods A total of 28 patients who underwent surgery for lumbar disc herniation were allocated into 2 groups: 12 patients (group A) operated by transflaval microdiscectomy, and 16 patients (group B) operated by tubular microdiscectomy. The serum concentration of total creatine phosphokinase was measured before surgery (creatine phosphokinase 1) and 1 day after surgery (creatine phosphokinase 2).Results There were 12 women and 16 men; the mean age of the patients and the mean duration of the surgery were respectively 49.5 years and 56 minutes for group A, and 47.3 years and 60 minutes for group B. The p-values of creatine phosphokinase 1, creatine phosphokinase 2 and the creatine–phosphokinase ratio were respectively 0,34; 0,31; and 0,57 (p < 0.05).Conclusion The present study demonstrated that there was no significant difference between tubular microdiscectomy and conventional microdiscectomy according to the analysis of the levels of creatine phosphokinase.
Keywords: enzima; hérnia; microdiscectomia; ciática; tubular